AKTUALISASI PEMBANGUNAN PARTISIPATIF DALAM FORUM KOMUNIKASI PEMBERDAYAAN PEREMPUAN DESA - Toto Sugito; Rili Windiasih; Adhi Iman Sulaiman (Jurusan Ilmu Komunkasi FISIP Universitas Jenderal Soedirman, 2018)
The research aims to cerat the model of communication forum for village women empowerment as the actualization of participative development (FPPD). The research used Participatory Rural Appration (PRA) research method that involves the role and potential of the community in a participatory to identify and find solutions to problems, and determine the needs that must be implemented by the community itself. Data were collected through Focus Group Discussion (FGD), interviews, observation, and documentation. Analysis of research used interactive analysis through reduction and presentation of data and conclusion. The research location in Sidaurip Village and Karangtawang Village, Cilacap Regency. The results showed that FPPD model have realization of participatory communication that important role in rural development to provide more opportunities for women in planning, implementation, and evaluation of empowerment programs and improving welfare.